Renal phenotype of young and old telomerase-deficient mice - Schildhorn, Carolin; Westhoff, Jens; Gretz, Norbert; Kränzlin, Bettina (Mechanisms of ageing and development, 2015)
Telomere shortening in the kidney explains the impaired regenerative capacity, but may not drive the ageing phenotype itself. We investigated kidneys from young and old Terc+/+ and Terc−/− mice of early (G1) and late (G4, G5) generations. Functional parameters declined and age-related morphological changes increased in late generation Terc−/− mice and with further age. Podocyte loss was only seen in old G4 Terc−/−. Whereas p21CIP1/WAF1 was highest in old G1 and G4 Terc−/−, telomere shortening and p16INK4a expression, also significantly associated with later generation young Terc−/−, were not further induced in old Terc−/− mice. Both, young and old late generation Terc−/−, showed increased pro-inflammatory cytokine levels. Young late generation Terc−/− animals show mild functional and histological abnormalities, the presence of cellular senescence explains their kidneys’ limited regenerative capacity. While these aspects resemble the situation seen in aged human kidneys, the lack of telomere shortening and p16INK4a induction in older Terc−/− animals differs from observations in old human kidneys and may result from clearance of senescent cells. This animal model is well suited to investigate the mechanisms of impaired renal regeneration in aged human kidney, but may not fully explain the natural course of the human renal ageing phenotype.
Gesehen am 19.11.2018
Available online 12 August 2015